Solve each of the following quadratic equations:

Given:

taking LCM

(3x + 4)(x + 4) = 5x2 + 15x + 10 cross multiplying

3x2 + 16x + 16 = 5x2 + 15x + 10

2x2 - x - 6 = 0

Using the splitting middle term - the middle term of the general equation is divided in two such values that:

Product = a.c

For the given equation a = 2 b = - 1 c = - 6

= 2. - 6 = - 12

And either of their sum or difference = b

= - 1

Thus the two terms are - 4 and 3

Difference = - 4 + 3 = - 1

Product = - 4.3 = 12

2x2 - x - 6 = 0

2x2 - 4x + 3x - 6 = 0

2x(x - 2) + 3(x - 2) = 0

(x - 2) (2x + 3) = 0

(x - 2) = 0 or (2x + 3) = 0

Hence the roots of equation are

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos
Quiz | Knowing the Nature of Roots44 mins
Take a Dip Into Quadratic graphs32 mins
Foundation | Practice Important Questions for Foundation54 mins
Nature of Roots of Quadratic EquationsFREE Class
Getting Familiar with Nature of Roots of Quadratic Equations51 mins
Quadratic Equation: Previous Year NTSE Questions32 mins
Champ Quiz | Quadratic Equation33 mins
Balance the Chemical Equations49 mins
Champ Quiz | Quadratic Equation48 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses